Jaringan Aktor dalam Program Percepatan Pendaftaran Tanah di Badan Pertanahan Nasional Kota Semarang - Ita Pujiastuti; Tri Yuningsih; Augustin Rina Herawati; Retno Sunu Astuti; Budi Puspo Priyadi; Teuku Afrizal (PERSPEKTIF, 2022)
Actor network is a collaboration that emphasizes the relationship or interaction between actors involved in a particular public affair to make the public affairs successful, it is very dependent on coordination between actors in finding a middle way to achieve common goals. The network of actors is very important and urgent in accelerating the implementation of the land registration acceleration program at the National Land Agency of Semarang City. Based on the Actor Network Theory (ANT) theory proposed by Bruno Latour in 1987, it has been used in various fields of knowledge, including the social field, with the concept of consensus building which was initiated where stakeholders interact, negotiate and have tolerance as the basis and used in this study to describe the model. network of actors in accelerating land registration as a form of public service. This study aims to identify and analyze the role of actors, as well as the network model of actors in the complete systematic land registration acceleration program in the city of Semarang. This study uses a qualitative descriptive method and the key instrument is the researcher (the researcher is the key informant). The results of this study indicate that the Semarang City Land Office is the main actor and acts as a mouthpiece for implementing policies, facilitators and coordinators. This study examines the development of policies for accelerating land registration in Indonesia in relation to network relationships between actors who influence policies in this field.